A Simple and Sensitive HPTLC Method for Simultaneous Determination of Metformin Hydrochloride and Sitagliptin Phosphate in Tablet Dosage Form - Darshana K. Modi; Punit B. Parejiya; Bhavesh H. Patel (Journal of Chemistry, 2013)
A simple, rapid, and precise high-performance thin-layer chromatographic (HPTLC) method for simultaneous estimation of two antidiabetic drugs, metformin hydrochloride and sitagliptin phosphate, in tablet dosage form has been developed and validated. Chromatography was performed on silica gel 60 F254 plates with butanol : water : glacial acetic acid (6 : 2 : 2, v/v/v) as mobile phase. This system gave a good resolution for metformin hydrochloride ( value of 0.35 ± 0.01) and sitagliptin phosphate ( value of 0.75 ± 0.01). Detection and quantification were carried out at 227 nm. The linear regression data for the calibration plot showed a good relationship with and 0.9991 for metformin hydrochloride and sitagliptin phosphate, respectively. The method was validated for precision and recovery. The limits of detection and quantification were 13.05 and 39.56 ng/μL for metformin hydrochloride and 2.65 and 8.03 ng/μL for sitagliptin phosphate, respectively. The amounts of the drugs in the marketed formulation were 99.86% and 98.91% for metformin hydrochloride and sitagliptin phosphate, respectively.